Primary omental infarction – a benign cause of acute abdomen - Pemmada, Vikas; Shetty, Athish; Koteshwar, Prakashini; Rajpurohit, Siddesh; Bhat, Ganesh (Pleura and peritoneum, 2024)
Omental infarction (OI) is an uncommon cause of acute abdominal pain. A high index of clinical suspicion is required for diagnosis of OI as the incidence is less than 1 %, presenting with abdominal pain. We report primary OI's clinical and radiological profile from a single tertiary care hospital in India. In this retrospective cross-sectional study, the electronic medical and radiology records of patients with abdominal pain were reviewed over seven years (2015-2022). Variables were systematically collected and analyzed. A total of 22 patients diagnosed with primary OI were included in this study. Male preponderance (63.6 %) was noted with a mean age of 47.45 years (SD ± 13.84; range: 18-72 years). Most patients belonged to class I obesity (according to the Asia-Pacific body mass index classification) with a mean BMI of 26.56 kg/m (SD ± 3.21 kg/m ). All patients had abdominal pain as the primary symptom, with a mean duration of 8.64 days (SD ± 10.15; range: 1-42 days). The most common locations of pain were the right hypochondrium (27.3 %) and diffuse (27.3 %), followed by the right iliac fossa (18.1 %). Most (95.45 %, n=21/22) patients were treated conservatively, and only one required surgical intervention. Primary OI is a rare and benign cause of acute abdomen. Obesity is a risk factor but does not correlate with the size or severity of OI. Radiological imaging, like a computed tomography (CT) scan, is essential for diagnosis. A conservative management line should be the first approach in treating primary OI before considering surgical options.